Evolutionary and population dynamics of host-parasitoid interactions - Tuda, M; Bonsall, M (1999)
The role of evolutionary dynamics in understanding host-parasitoid interactions is interlinked with the population dynamics of these interactions. Here, we address the problems in coupling evolutionary and population dynamics of host-parasitoid interactions. We review previous theoretical and empirical studies and show that evolution can alter the ecological dynamics of a host-parasitoid interaction. Whether evolution stabilizes or destabilizes the interaction depends on the direction of evolutionary changes, which are affected by ecological, physiological, and genetic details of the insect biology. We examine the effect of life history correlations on population persistence and stability, embedding two types, one of which is competitively inferior but superior in encapsulation (for parasitoid, virulence), in a Nicholson-Bailey model with intraspecific resource competition for host. If a trade-off exists between intraspecific competitive ability and encapsulation (or virulence, as a countermeasure) in both the host and parasitoid, the trade-off or even positive correlation in the parasitoid is less influential to ecological stability than the trade-off in the host. We comment on the bearing this work has on the broader issues of understanding host-parasitoid interactions, including long-term biological control.